Enhanced light extraction from organic light-emitting diodes using a quasi-periodic nano-structure. (28th December 2018) - Lee, Ju Sung; Shim, Yong Sub; Park, Chan Hyuk; Hwang, Ha; Park, Cheol Hwee; Joo, Chul Woong; Park, Young Wook; Lee, Jonghee; Ju, Byeong-Kwon
Abstract: Organic light-emitting diodes with a quasi-periodic nano-structure (QPS) were fabricated via a combination of laser interference lithography (LIL) and reactive ion etching (RIE). The LIL process was used to generate a periodic pattern, whereas the RIE process was used as a supplement to add randomness to the periodic pattern. The period of the fabricated periodic pattern was determined by finite difference time domain solutions. The height and density of the QPS were controlled by the RIE etching time and were optimized. The resulting quasi-periodic nanostructure comprised silicon dioxide (SiO2 ) with a low refractive index ( n = 1.4–1.5), and an external quantum efficiency enhancement of 18% was achieved using the QPS device, without any viewing angle problems or spectral distortion, which are serious drawbacks of periodic patterns.